Pengaruh Teknologi Informasi terhadap Efisiensi Operasional dalam Manajemen Logistik - Aufaa, Rayhan Dhevano (Peneliti.net, 2024)
This research aims to reveal the significant influence of informationtechnology on improving operational efficiency in logistics management.With a focus on technological innovations such as the Internet of Things(IoT), big data analytics, and blockchain, this research seeks to assesshow these technologies can optimize operational processes, reduce costs,and improve response speed in the logistics industry. This research usesthe literature study method to examine the effect of informationtechnology on operational efficiency in logistics management. Thisresearch has revealed the important role that information technology (IT)plays in improving operational efficiency in the field of logisticsmanagement. With IT advancements, companies can speed up processes,improve accuracy, and reduce operational costs